Enhancing Strategic Sports Analysis: A Semi-Graphical Single Display for Pakistan Super League (PSL) 2024 Outcomes Visualization of Outcomes of PSL-2024 Matches on a Single Display (Contemporary Journal of Social Science Review, 2025)
The visualization of data is causing a revolution in study across a variety of sectors, making complex information easier to understand. In the field of sports, data visualization has developed beyond its primary function in entertainment, acquiring a large role as a powerful instrument for players, coaches, and fans to analyze performance and design strategic approaches. This is a huge development. The purpose of this research is to provide a novel "semi-graphical display" that has been built expressly to graphically represent the schedule and results of all matches for the Pakistan Super League (PSL) 2024, which is the ninth edition of the league. Utilizing statistics from the 2024 Pakistan Super League (PSL) was how the effectiveness of the semi-graphical presentation was shown. Six teams are competing in the Premier League of Pakistan (PSL), and their names are as follows: Islamabad United (IU), Karachi Kings (KK), Lahore Qalandars (LQ), Multan Sultans (MS), Peshawar Zalmi (PZ), and Quetta Gladiators (QG). The Philippine Super League (PSL) is being used as a case study in this particular context; however, the relevance of this presentation can be expanded to other sports leagues that have a comparable number of players. In addition to this, the article investigates the various sporting contexts in which the display might be utilized.